2016
DOI: 10.1158/1541-7786.mcr-16-0251
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoskeletal Adapter Protein Spinophilin Regulates Invadopodia Dynamics and Tumor Cell Invasion in Glioblastoma

Abstract: Glioblastoma (GBM) is a primary brain cancer that is resistant to all treatment modalities. This resistance is due, in large part, to invasive cancer cells that disperse from the main tumor site, escape surgical resection, and contribute to recurrent secondary lesions. The adhesion and signaling mechanisms that drive GBM cell invasion remain enigmatic, and as a result there are no effective anti-invasive clinical therapies. Here we have characterized a novel adhesion and signaling pathway comprised of the inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…These specialized membrane structures are able to reach lengths greater than 2 μm, with diameters ranging from 0.1 to 0.8 μm [11] , and function to degrade the surrounding matrix through the action of transmembrane proteases, such as MT1-MMP, and secreted proteases, such as MMP-2 and MMP-9 [12] , ultimately facilitating malignant cell invasion through the modified surrounding extracellular matrix (ECM). The presence of invadopodia in glioma cells lines and cells harvested from GBM patient specimens has been previously documented [11] , [13] , [14] , suggesting that they may potentially play a role in glioma cell invasion. Importantly, we have previously shown that the expression levels of an invadopodia regulator, Tks5, in glioma patient biopsies may be of prognostic significance [15] .…”
Section: Introductionmentioning
confidence: 82%
“…These specialized membrane structures are able to reach lengths greater than 2 μm, with diameters ranging from 0.1 to 0.8 μm [11] , and function to degrade the surrounding matrix through the action of transmembrane proteases, such as MT1-MMP, and secreted proteases, such as MMP-2 and MMP-9 [12] , ultimately facilitating malignant cell invasion through the modified surrounding extracellular matrix (ECM). The presence of invadopodia in glioma cells lines and cells harvested from GBM patient specimens has been previously documented [11] , [13] , [14] , suggesting that they may potentially play a role in glioma cell invasion. Importantly, we have previously shown that the expression levels of an invadopodia regulator, Tks5, in glioma patient biopsies may be of prognostic significance [15] .…”
Section: Introductionmentioning
confidence: 82%
“…The origin of the force at play when αVβ8 is involved is less clear because the cytoplasmic tail of β8 does not couple with the actin cytoskeleton and is not required for TGF-β activation in transfected cells (31). However, several studies in cell lines of various origins have now reported interaction between the short β8 tail and cytoplasmic signaling or adaptor molecules, which could in turn directly or indirectly interact with the cytoskeleton (39)(40)(41)(42)(43). In TCR-stimulated human Tregs, β8 may interact with similar proteins, which would provide the traction forces required for the mechanical opening of the LAP.…”
Section: Discussionmentioning
confidence: 99%
“…5962 We have reported previously that αvβ8 integrin-mediated signaling via Rho GTPases regulatory factors is essential for tumor cell invasion in the brain. 42,63,64 It will be interesting to determine whether αvβ8 integrin or its intracellular signaling effectors are differentially regulated in GSCs following surgery and anti-vascular therapies, thus contributing to tumor recurrence and/or invasion. These studies may extend beyond GBM; for example, ITGB8 expression is upregulated in peripheral nerve sheath tumors, 65 and in brain metastases, 66 suggesting that targeting this integrin may impact tumor growth in other cancer types.…”
Section: Discussionmentioning
confidence: 99%